2019
DOI: 10.2136/sssaj2019.03.0062
|View full text |Cite
|
Sign up to set email alerts
|

Asymbiotic Nitrogen Fixation is Greater in Soils under Long‐Term No‐Till Versus Conventional Tillage

Abstract: A series of N‐rate experiments previously conducted in spring wheat, corn, and sunflower in North Dakota indicated that less N was required when fields were in six years or more continuous no‐till compared to conventional till. The objective of this study was to determine whether part of the reason for the decreased requirement for N was the greater activity of asymbiotic N‐fixing organisms. Twelve paired‐samplings were conducted in 2018. A surface 0‐ to 5‐cm deep sample was obtained in a long‐term no‐till fie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…One of the reasons why transitional no‐till sites were chosen for this study was that a trend to greater N‐fixing activity was expected over time. However, each season was unique due to soil moisture and temperature regime, and although previous work indicated that long‐term no‐till supports greater activity compared to conventional tillage (Franzen et al., 2019), the trend toward greater N‐fixation is likely to be observed at a longer time‐span than this 3‐year sampling study was capable of showing. One might speculate that it would take 10 years to produce enough data to discern a trend because of year‐to‐year variation in rainfall patterns and spring warm‐up conditions.…”
Section: Resultsmentioning
confidence: 57%
See 3 more Smart Citations
“…One of the reasons why transitional no‐till sites were chosen for this study was that a trend to greater N‐fixing activity was expected over time. However, each season was unique due to soil moisture and temperature regime, and although previous work indicated that long‐term no‐till supports greater activity compared to conventional tillage (Franzen et al., 2019), the trend toward greater N‐fixation is likely to be observed at a longer time‐span than this 3‐year sampling study was capable of showing. One might speculate that it would take 10 years to produce enough data to discern a trend because of year‐to‐year variation in rainfall patterns and spring warm‐up conditions.…”
Section: Resultsmentioning
confidence: 57%
“…One of the reasons why transitional no-till sites were chosen for this study was that a trend to greater N-fixing activity was expected over time. However, each season was unique due to soil moisture and temperature regime, and although previous work indicated that long-term no-till supports greater activity compared to conventional tillage (Franzen et al, 2019), the trend toward greater N-fixation is likely to be observed at a F I G U R E 1 0 Exponential relationship between N-fixing activity and mean air temperature, 30 days preceding sampling. longer time-span than this 3-year sampling study was capable of showing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Obscuribacteria, a family within the phylum Cyanobacteria; Nitrosotaleaceae a family of archaea that can oxidize ammonia (Prosser and Nicol, 2015); and Phycisphaeraceaea, a family potentially involved in anammox (Rios-Del Toro, et al, 2018), were all higher in NT treatments compared to MP. Increased activity of free-living N2-fixing microorganisms may also occur in NT soils (Franzen et al, 2019). Changes to community composition in bulk soils managed under NT favor bacteria and archaea that cycle N and bypass the denitrification pathway.…”
Section: Tillage Intensity Bacterial-archaeal Diversity and Denitrifi...mentioning
confidence: 99%